Pittsburgh Response to Endovascular therapy (PRE) score: optimizing patient selection for endovascular therapy for large vessel occlusion strokes. (15th October 2014) - Rangaraju, Srikant; Aghaebrahim, Amin; Streib, Christopher; Sun, Chung-Huan; Ribo, Marc; Muchada, Marion; Nogueira, Raul; Frankel, Michael; Gupta, Rishi; Jadhav, Ashutosh; Jovin, Tudor G
Abstract : Background: Endovascular therapy seems to benefit a subset of patients with large vessel occlusion strokes. We aimed to develop a clinically useful tool to identify patients who are likely to benefit from endovascular therapy. Methods: In a derivation cohort of consecutively treated patients with anterior circulation large vessel occlusion (Grady Memorial Hospital, N=247), independent predictors (p<0.1) of good outcome (90-day modified Rankin scale score (mRS) 0–2) were determined using logistic regression to derive the Pittsburgh Response to Endovascular therapy (PRE) score as a predictor of good outcome. The PRE score was validated in two institutional cohorts (University of Pittsburgh Medical Center (UPMC): N=393; Unitat d'Ictus Vall d'Hebron: N=204) and its discriminative power for good outcome was compared with other validated tools. Benefit of successful recanalization was assessed in PRE score groups. Results: Independent predictors of good outcome in the derivation cohort (age, baseline National Institute of Health Stroke Scale (NIHSS) score and Alberta Stroke Program Early CT Score (ASPECTS)) were used in the model: PRE score=age (years)+2×NIHSS−10×ASPECTS. PRE score was highly predictive of good outcome in the derivation cohort (area under the curve (AUC)=0.79) and validation cohorts (UPMC: AUC=0.79; UIVH: AUC=0.72) with comparable rates of good outcome in all PRE risk quartiles. PRE was superior to Totaled Health Risks In Vascular Events (THRIVE) (p=0.03) and Stroke Prognostication using Age and NIHSS (SPAN) (p=0.007), with a trend towards superiority to Houston Intra-Arterial Therapy 2 (HIAT2) (p=0.06) and iSCORE (p=0.051) in predicting good outcomes. Better outcomes were associated with successful recanalization in patients with PRE scores −24 to +49 but not in patients with PRE scores <−24 or ≥50. Conclusions: The PRE score is a validated tool that predicts outcomes and may facilitate patient selection for endovascular therapy in anterior circulation large vessel occlusions.